(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Preschool education, which is one of the first and main stages in the formation of personality, plays an important role in the physical development of children, as well as in their mental development as a person. Emphasizing the importance of the preschool age in the socialization of children, psychologist RS Nemov divides this period into three stages [R.S.N., 193]. That is: 1) stage of emotional self-management (3-4 years);2) stage of moral self-government (4-5 years);3) the stage of formation of personal-practical qualities (5-6 years).Indeed, observing the activities of preschoolers at the age of 3-4 years makes an emotional assessment of the events that take place around them. For example, if something happens to them that they don’t like, they protest, get upset, and even cry. On the contrary, they rejoice when what happens to them is pleasant, they “report” it to their peers, parents, other family members, or caregivers, and they laugh out loud. By the age of 3, children develop active speech and begin to speak fluently. Speech growth lays the groundwork for mental development. By interacting with those around them, they gain a better, deeper understanding of the environment, nature, and those around them. This, in turn, helps to develop the psyche of children of preschool age. During this period, their mobility, perception of material existence, and speech develop rapidly.Their perception is real object perception, they think about the objects they perceive, the things they are familiar with. The child’s perception in this period is expressed, first of all, in his attitude to objects. In the preschool age, speech develops in proportion to the development of children’s consciousness. Between the ages of 3 and 6, children learn almost all of the words that are constantly used in daily life and the simple grammatical techniques of the language.In preschool, children’s active communication with others - peers and adults - contributes to the growth of their speech. As a result, at this age, they are able to tell in detail about events they have performed, witnessed, or heard from others. Relationships with others have a positive effect on the formation of their personality. As a result of this influence, they make spiritual and moral judgments about social realities.